Pollination of flowers of the San Andreas strawberry cultivar - Miranda, Priscila Silva; Lima, Zilda Cristina Malheiros; Pérez-Maluf, Raquel; Moreira, Aldenise Alves (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to determine the optimal day for pollinating the flowers of the San Andreas strawberry cultivar after flower anthesis. The study was carried out in two periods (summer and fall), on a commercial farm. A total of 12 flower buds were monitored and photographed in each of the following 11 treatments: manual cross-pollination (MCP) on the first to fifth day after flower anthesis (MCP1 to MCP5), natural pollination (NP) on the first to fifth day after flower anthesis (NP1 to NP5), and self-pollination. After pollination, the flowers were bagged until the development and maturation of the flower receptacle. Subsequently, the fruits were harvested, quantified, and subjected to evaluations to determine biometry, degree of deformity, and the percentage of fertilized achenes. The flowers of the San Andreas cultivar remain open during five days, when the beginning of the development of the flower receptacle can already be observed. The optimal days for strawberry flower pollination through MCP or NP are the first two days after anthesis.